Human Resource Development Management in An Effort to Improve The Quality of Education at Pesantren Darul Arqom Wiradesa Pekalongan - Kistin toniyah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This research was conducted to find out how the implementation of human resource development management in efforts to improve the quality of education in the Pesantren Darul Arqom Wiradesa Pekalongan, know how the role of management of human resource development in efforts to improve the quality of education in Darul Arqom Wiradesa Pekalongan, as well as knowing what factors which is a supporter and obstacle in the implementation of management of human resource development in the Pesantren Darul Arqom Wiradesa Pekalongan. This research is a field research with a qualitative approach. Data generated from interviews, observations, and documentation. While the steps of data analysis in this study are the processes, data collection, data reduction, data display, drawing conclusions and verification. From the research results it is known that managerially and operationally, the function of human resource management has been carried out in Darul Arqom Wiradesa Pekalongan and proved to play a very positive role. This can be seen in the process, implementation, and procedures in the stages of planning, management, procurement of labor, compensation, development and training, evaluation and termination of work. Although there are still some minor evaluation notes and a few inhibiting factors that should be resolved and become a concern for improvement in the future. Keywords: Management, Human Resources, Quality of Education